Management of a Severe Case of Osteogenesis Imperfecta in Ghana: Evaluation of Outcome - D, Konadu-Yeboah; G, Asante; H, Okrah; J, Sobotie; ANK, Okleme; ST, Boadi (Archives of Clinical and Medical Case Reports, 2024)
Introduction: Osteogenesis imperfecta is the most common genetic disorder of bone and is characterised by growth retardation, bone fragility, deformity and joint hyperlaxity. Severe disease causes pain and limitation of function. Case Report: An 8-year old male with multiple lower limb deformities, growth retardation and inability to stand upright and walk since birth. Conclusion: Surgery in a child with severe osteogenesis imperfecta with multiple lower limb deformities could be safe, effective and improves function. At 3 years following surgery, the child’s lower limbs remain well aligned, he is a community ambulator and is able to perform self-care: toileting, dressing and grooming.